PELATIHAN BAHASA ISYARAT BAGI MAHASISWA UNIVERSITAS MUHAMMADIYAH PRINGSEWU - Arum Arupi Kusnindar; Ainur Rosidah (Bajang Institute, 2022)
The law has guaranteed people with disabilities to get fair treatment in all aspects of life. So far, people with disabilities, especially the deaf, have had problems participating in various activities due to the unavailability of a sign language interpreter. This Community Service activity aims to produce new sign language translators who are able to help deaf people participate in general activities. This service is carried out by holding sign language classes for 10 weeks. Classes are attended by elementary, middle, high school, and lecturers as well as young people who want to dedicate themselves as companions with disabilities